Pengaruh Lifestyle dan Green Knowledge Terhadap Green Purchase Behavior yang Dimediasi Good Purchase Intention - Laela, Laela; Mohungo, Yolanda (Al-Buhuts, 2025)
This study aims to analyze the influence of Lifestyle and Green Knowledge on Green Purchase Behaviour with Green Purchase Intention as a mediating variable. The study is motivated by the growing public awareness of environmental issues and the importance of understanding the factors that drive environmentally friendly purchasing behavior. A quantitative approach was used, employing Structural Equation Modeling (SEM) as the analytical technique. Data were collected through a questionnaire distributed to 100 respondents with experience in purchasing eco-friendly products. The results show that lifestyle does not have a direct effect on green purchase behaviour but has a positive effect on green purchase intention. Green knowledge has a positive effect on green purchase behaviour but does not influence green purchase intention. Furthermore, green purchase intention is found to significantly mediate the relationship between lifestyle and green purchase behaviour, but not the relationship between green knowledge and green purchase behaviour. These findings reinforce the importance of building environmentally friendly purchase intentions through consumer lifestyle in order to enhance green purchasing behavior.